The crisis of accounting education in the U.S. - Krasna, Olena (My University, 2014)
The global marketplace is changing. Businesses rely more and more on changing technology. The companies, services and industries that luel economic growth also are evolving. In this new marketplace, traditional accountants are a dying breed. Technology has made preparing and disseminating financial information so inexpensive anyone with the right software can produce basic data. Yet, many accounting educators have failed to restructure accounting curriculum to equip graduates with the tools and expertise they need in today’s business world. As a result, fewer and less-qualified students choose accounting careers, and the future of accounting schools as top-tier providers of business graduates is at risk.
Keywords: accounting; education; crisis; бухгалтерський облік; освіта; криза